The effects of Citrus mitis Blanco (Calamansi) fruit tissue extracts on the germination of its seeds. - Danugo, Leslie F.
The present study attempted to determine if the extracts of the fruit tissues of Citrus mitis Blanco (calamansi) such as the epicarp, mesocarp, endocarp, and the placenta, have inhibitory effects on the germination of its seeds. The particular tissue that showed the highest inhibitory effect was identified. This was done by germinating 20 seeds in a Petri dish containing an extract. Each treatment has three replicates and was observed after 11.5 days. Data showed that the different extracts from Citrus mitis Blanco fruit brought about a lower percentage of germination to the seeds. The order of inhibitory effect from highest to lowest was, epicarp > mesocarp > endocarp > placenta. Chemical analysis conducted also found the presence of natural chemical inhibitors. Amygdalin was present in the epicarp tissue, while aldehydes were present in all parts that sorround the seeds.